Security of Central Asia in the Context of Globalization: A Socio-Philosophical Analysis of the Anthropology of Terrorism - Jakhongir Boybutayev (International Journal on Integrated Education, 2026)
This article analyzes the factors threatening Central Asian security in the context of globalization based on the anthropology of terrorism and socio-philosophical approaches. The aim of the study is to identify the interconnectedness of external (global), regional, and anthropological factors affecting regional security, as well as to substantiate their impact on the relationship between man, society, and the state from a socio-philosophical perspective. The study employed historical-comparative, systematic, comparative-analytical, and socio-philosophical analysis, as well as approaches from the anthropology of terrorism and methods of synthesis and conceptual modeling. The article examines how security threats in the region manifest as a multi-level social system formed as a result of the interaction of global, regional, and anthropological factors. It also reveals that identity crisis, social inequality, value transformation, radicalization processes, and human security are important social factors that directly affect stability in the region.